2019
DOI: 10.1021/acsami.9b05244
|View full text |Cite
|
Sign up to set email alerts
|

Improving Carrier-Transport Properties of CZTS by Mg Incorporation with Spray Pyrolysis

Abstract: Improving carrier-transport properties of CZTS byMg incorporation with spray pyrolysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 66 publications
1
28
0
Order By: Relevance
“…[ 22 ] However, due to serious carrier recombination, pristine CZTS actually exhibits poor PEC activity. [ 23 ] Various strategies have been applied to alleviate the recombination in pristine CZTS, such as p ‐ n junction construction [ 24 ] and cation substitution. [ 25 ] For example, Wong et al.…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] However, due to serious carrier recombination, pristine CZTS actually exhibits poor PEC activity. [ 23 ] Various strategies have been applied to alleviate the recombination in pristine CZTS, such as p ‐ n junction construction [ 24 ] and cation substitution. [ 25 ] For example, Wong et al.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 In addition to these issues, the kesterite based photovoltaic devices suffer from severe band tailing, which particularly reduces the open circuit voltage (V oc ) of solar cells. 14 Rey et al reported the origin of band-tails in kesterite materials and showed that the large band tailing causes voltage losses that limit the efficiency of kesterite-based devices. 3,15 However, there have been recent efforts of using single or double cation substitution strategies to control band tailing in CZTS.…”
Section: Introductionmentioning
confidence: 99%
“…17 Lie et al also observed that the incorporation of Mg in Cu 2 ZnSnS 4 to form Cu 2 Mg x Zn 1Àx SnS 4 (varying x from 0.0 to 1.0) could suppress these defects and improve the open circuit voltage. 14 Recently, Dhawale et al reported an improvement in the V oc -deficit mainly due to the reduced band tailing obtained by controlling the Ge/(Sn + Se) ratio. 18 Nagaya et al reported the advantages of Ge in CZTS, 19 with a very small tail state formed in CZGSe compared to the large band tailing observed in CZTS and CZTSe.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other synthesis methods such as microwave-assisted, plasma-assisted synthesis and spray pyrolysis can offer easier procedure and faster reaction kinetics compared to other solution-based methods; thus, they are usually used to increase the production yield. [36][37][38] These techniques are alternative methods for the preparation of high-performance C-TMO hybrids. Notably, the combination of two or more synthetic methods are often employed to support the complex interaction between the surface oxygen functionality of TMO and the carbon network, including heteroatoms such as O, N and S, in which the carbon material anchors the TMO covalently through the formation of MÀ O-C/N/S bond.…”
Section: Synthetic Methods For the Preparation Of C-tmo Hybrid Composmentioning
confidence: 99%